Epibiotic rotifers of Gammarus pulex (L.) (Crustacea, Amphipoda), with descriptions of two new species and notes on the terminology of the trophi - Smet, Willem H. De; Verolet, Michel (Zootaxa, 2016)
The epibiotic rotifers of a Gammarus pulex (L.) collection from the Ardèche, France are reported. Four species were found, of which Cephalodella jersabeki n. sp. and Proales gammaricola n. sp. are new to science and described. The other species, Dicranophorus cambari Wulfert and Embata laticeps (Murray), are commented upon. SEM micrographs of the trophi are presented, and a new or amended terminology is proposed for some diagnostic trophi parts.